Perancangan set meja makan minimalis berkonsep Japandi Style - Nurhadi, Irvan; Susila, Dwi Agus; Ariyanto, Ariyanto (Institut Seni Indonesia Yogyakarta, 2025)
This research aims to design a minimalist dining table set using the Japandi style concept for the dining room. In the era of rapid growth in the global furniture industry, where the need for an efficient dining room is indispensable, the Japandi style concept was chosen for its flexibility in adjusting to the size of the space. This dining table set is designed to be modular when installed according to the user's needs, maximizing the efficiency of the dining room without compromising aesthetics. This research employs a qualitative method with a Design Thinking approach, involving five stages: empathize, define, ideate, prototype, and test. Teak wood was chosen as the primary material due to its durability and aesthetic value of its fibers. The Japandi style concept design not only meets the needs of the dining room but also supports the principle of sustainability through the use of durable and environmentally friendly materials. The results of the study show that the design with the Japandi style concept is effective in optimizing the dining room.